2017
DOI: 10.14202/vetworld.2017.1083-1093
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption-ionization-time-of-flight mass spectrometry as a reliable proteomic method for characterization of Escherichia coli and Salmonella isolates

Abstract: Aim:Identification of pathogenic clinical bacterial isolates is mainly dependent on phenotypic and genotypic characteristics of the microorganisms. These conventional methods are costive, time-consuming, and need special skills and training. An alternative, mass spectral (proteomics) analysis method for identification of clinical bacterial isolates has been recognized as a rapid, reliable, and economical method for identification. This study was aimed to evaluate and compare the performance, sensitivity and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…It is envisaged that molecular identification through MALDI-TOF MS will rapidly establish a robust position for surveillance of microbial pathogens in the complex interwoven network of origin, producers, traders and consumers. Our results are consistent with previous work by Shell et al (2017) where it was stated that MALDI-TOF MS showed significant promise in E. coli and Salmonella identification on genus and species levels and can be also used as a tool for sub species and serovar typing, but it will require additional studies and modifications to existing protocols and commercial and the extended database. The identification using MALDI-TOF MS method could analyze pure positive culture rapidly (may be within minutes especially when direct cultural identification methods used rather than ethanol: Formic acid extraction method) and also reliable manner.…”
Section: Discussionsupporting
confidence: 91%
“…It is envisaged that molecular identification through MALDI-TOF MS will rapidly establish a robust position for surveillance of microbial pathogens in the complex interwoven network of origin, producers, traders and consumers. Our results are consistent with previous work by Shell et al (2017) where it was stated that MALDI-TOF MS showed significant promise in E. coli and Salmonella identification on genus and species levels and can be also used as a tool for sub species and serovar typing, but it will require additional studies and modifications to existing protocols and commercial and the extended database. The identification using MALDI-TOF MS method could analyze pure positive culture rapidly (may be within minutes especially when direct cultural identification methods used rather than ethanol: Formic acid extraction method) and also reliable manner.…”
Section: Discussionsupporting
confidence: 91%
“…Identification of the bacterial isolates was executed using a Bruker MALDI biotyper (Bruker Daltonics) following standard methods (Bujnakova et al, 2013;Dec et al, 2016;Shell et al, 2017). The mass spectra were handled by the MALDI Biotyper 3.0 software package (Bruker, Leipzig, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative analysis of microbial isolates was performed using the method described by Shell et al [49] using MALDI-TOF mass spectrometry (Bruker Daltonics, Bremen, Germany). The generated spectra were analysed on a MALDI-TOF Microflex LT instrument (Bruker Daltonics, Bremen, Germany) using Flex Control 3.4 software.…”
Section: Microbiological Analysismentioning
confidence: 99%